Empowerment or repression? Opening up questions of identification and surveillance in Brazil through a case of 'identity fraud' - Murakami Wood, David (2009)
A real but typical case of identity fraud is used to open up the complex web of identification systems in Brazil. It is argued that identification has two poles related to the nature of citizenship—repression and inclusion—and that reactions from citizens to new identification schemes can be attributed to how they view the purpose of the cards in these terms. In Brazil, a sense of inclusion and citizenship based on a fear of anonymity and exclusion predominates leading to widespread support amongst even critics of state activities. However, this may be undermined by the lack of state preparation for an information society, particularly the absence of meaningful data protection laws.